2015
DOI: 10.1021/acscatal.5b00411
|View full text |Cite
|
Sign up to set email alerts
|

MIL-101 as Reusable Solid Catalyst for Autoxidation of Benzylic Hydrocarbons in the Absence of Additional Oxidizing Reagents

Abstract: Materiaux de l'Institute Lavosier-101 (MIL-101) promotes benzylic oxidation of hydrocarbons exclusively by molecular oxygen in the absence of any other oxidizing reagent or initiator. Using indane as model compound, the selectivity toward the wanted ol/one mixture is higher for MIL-101(Cr) (87% selectivity at 30% conversion) than for MIL-101(Fe) (71% selectivity at 30% conversion), a fact that was associated with the preferential adsorption of indane within the pore system. Product distribution and quenching e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 56 publications
(103 reference statements)
12
120
0
Order By: Relevance
“…9, 46 BET surface areas and pore volumes obtained after synthesis were around 1,850 m 2 g -1 and 1.12 cm 3 , respectively. 23 These differences can influence the interaction of the MOF with molecular oxygen and can also modify the polarity of the internal voids of the material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9, 46 BET surface areas and pore volumes obtained after synthesis were around 1,850 m 2 g -1 and 1.12 cm 3 , respectively. 23 These differences can influence the interaction of the MOF with molecular oxygen and can also modify the polarity of the internal voids of the material.…”
Section: Resultsmentioning
confidence: 99%
“…23 In addition, MIL-101 solids exhibit large pores (free diameters of 29 and 34 Å) with microporous windows of 12 and 16 Å, respectively, allowing the adsorption of DBT derivatives into their cavities. It has been frequently observed that, in order to be used as catalyst, MOFs have to be submitted to an activation process to remove co-adsorbed water and solvent molecules and to generate coordinatively unsaturated sites around the metal centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1‐hydroperoxy IB cannot be quantified by GC owing to its decomposition. Therefore, the reaction mixture was treated with triphenylphosphine at 80 °C to promote decomposition of the hydroperoxide and, then, the formation 1‐hydroxy‐1‐IB, together with 1‐phenyl‐1‐isobutanol was quantified together with triphenylphosphine oxide and 1‐phenyl‐2‐methyl‐1‐propanol . Benzoic acid is a secondary product, coming from oxidation of phenyl isopropyl ketone.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39] Normally, these reactions are performed at high temperatures to activate the stable sp 3 -hybridized CÀH bonds. [28][29][30][31][32][33][34][35][36][37][38][39] Normally, these reactions are performed at high temperatures to activate the stable sp 3 -hybridized CÀH bonds.…”
Section: Introductionmentioning
confidence: 99%